Association of vascular endothelial growth factor (VEGF) protein levels and gene polymorphism with the risk of chronic kidney disease. Issue 1 (31st December 2023) - Liu, Yipin; Hong, Kai; Weng, Wenjuan; Huang, Shuangyi; Zhou, Tianbiao
ABSTRACT: Vascular endothelial growth factor (VEGF) is a heparin-specific growth factor specific for vascular endothelial cells and induces angiogenesis via binding to vascular endothelial growth factor receptor (VEGFR). Chronic kidney disease (CKD), accompanied by microvascular disease, is recognized as an irreversible reduction of renal function. The effects of VEGF on CKD risk were evaluated in this study. 121 CKD patients and 50 healthy volunteers were evaluated in the current study. Data mining using the China Biological Medicine (CBM) and NCBI/PubMed databases, was performed and applicable investigations were pursued. Pooled mean differences (MD) and pooled odds ratios (OR), with corresponding confidence intervals (CIs), were calculated by meta-analysis. The levels of Scr, BUN and VEGF in the CKD group were significantly higher, when compared with the control group (P < 0.01). For the meta-analysis, thirteen articles and our current study were evaluated. VEGF levels was found to be associated with CKD risk (P < 0.00001). In the sub-group meta-analysis, we found that the pooled MD of VEGF levels was related to the early CKD group, although the difference was not notable. However, the meta-analysis itself indicated that the pooled MD of VEGF levels were in accordance with severe CKD group (P < 0.00001). Furthermore, VEGF +936C/T T allele was not associated with CKD risk (P = 0.69). VEGF levels are apparently associated with CKD risk, especially in more severe CKD. Gene polymorphism analysis indicates that the VEGF +936C/T T allele is not associated with CKD risk.